Tinjauan Pelaksanaan Pengelolaan Visum et Repertum Berdasarkan Prosedur Tetap di Rumah Sakit X Kota Banjar - Heryani, Indah; Sugiarti, Ida (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2025)
Visum et Repertum is an official medical document made at the request of investigators for legal evidence purposes. However, less than optimal management of Visum et Repertum such as improper procedures, incomplete information, and delays in the process can hinder the legal process. This study uses a descriptive qualitative method to understand the implementation of Visum et Repertum management based on Standard Operating Procedure (SOP) at Hospital X, Banjar City. Qualitative research emphasizes understanding natural phenomena that occur in the field so that it is more naturalistic. The descriptive method functions to provide a clear picture of the object being studied without conducting an analysis that produces general conclusions. Thus, this study aims to describe in detail how the management of the Visum et Repertum form is carried out in accordance with the established SOP. The making of Visum et Repertum at Hospital X, Banjar City has been in accordance with the applicable SOP, there are several problems faced by officers in implementing the making of Visum et Repertum. The most requests for Visum et Repertum come from cases of misuse with a total percentage of 45.25% of the total number of cases. There are conformities and non-conformities in the implementation of the making of Visum et Repertum. It is expected that officers can improve the implementation of procedures that are not yet appropriate so that services can be carried out optimally.